Hypogammaglobulinemia after rituximab for rheumatoid arthritis is not rare and is related with good response: 13 years real-life experience. (11th November 2020) - Evangelatos, Gerasimos; Fragoulis, George E; Klavdianou, Kalliopi; Moschopoulou, Melina; Vassilopoulos, Dimitrios; Iliopoulos, Alexios
Abstract: Objectives: Rituximab (RTX) use in the treatment of RA can be complicated by decrease in IgG, IgM or IgA levels (hypogammaglobulinemia-HGG). The aim of this study was to define the frequency of HGG in RA patients treated with RTX and to identify associations between its occurrence and patients' characteristics, disease outcomes and serious infections rate. Methods: RA patients treated with RTX in two rheumatology centers from January 2007 to January 2020 were retrospectively examined. Demographical, clinical and laboratory parameters were recorded at baseline and at last visit. Results: Eighty-three patients (84.3% females) with a mean age of 63.2 years were enrolled. They had baseline DAS28(CRP) of 5.2 (1.1) and received a median (range) of 8 (2–20) RTX cycles. A total of 43.4%, 24.1% and 31.3% developed 'any HGG', 'low IgG' and 'low IgM', respectively. Lower baseline IgG and IgM levels were predictors of 'low IgG' and 'low IgM' occurrence, respectively. Patients who developed 'low IgM' exhibited lower DAS28(CRP) and increased rates of remission and low disease activity compared with those with normal IgM levels. Patients who maintained normal IgG were receiving methotrexate more frequently. No differences were observed in serious infections rate among subgroups. Conclusion: HGG occurred in 43% of RTX-treated patients. Patients who developed low IgG or low IgM had lower baseline levels than those who did not. Concomitant DMARD and corticosteroid therapy was not associated with HGG. Low IgM, but not low IgG, development was associated with better disease outcomes. HGG was not associated with an increased incidence of serious infections.